A Critical Review on the Book ‘Majnun: The Madman in Medieval Islamic Society’ - Behzad Karimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Madness is one of the less-discussed issues in the social and medical history of Muslim societies in the Islamic Middle Ages. Madness until two or three decades ago was mostly considered as a mental illness by medical history researchers. But with the introduction of new social approaches to medical phenomena, we gradually see a stream of research that examines medical issues beyond the known boundaries of medical knowledge and in an interdisciplinary space that has produced some works. One of the few works that within this framework has extensively analyzed the history of madness in Islamic societies is Majnun: The Madman in Medieval Islamic Society by Michael W. Dols. In this book, he has extensively explored the subject of insanity in three different medical, social-historical, and legal/religious perspectives, relying on a variety of sources. However, this work has some defects for a variety of reasons, including the author’s partialism approach, overwhelming data on madness and being caught in the trap of a European-oriented Orientalist approach that in some cases has produced inappropriate generalizations.